Impact of tele-exercise on quality of life, physical fitness, functional capacity and strength in different adult populations: a systematic review of clinical trials - Nuno Domingos Garrido; Nuno Domingos Garrido; Victor Machado Reis; Victor Machado Reis; José Manuel Vilaça-Alves; José Manuel Vilaça-Alves; Gabriela Chaves Lucas; Ismael Lima Godinho; Rafael Peixoto; Alberto Fucarino; Manuela Cantoia; Enzo Iuliano; et al. (Frontiers in Sports and Active Living)
IntroductionThis study aimed to review the impact of tele-exercise on different adult populations, comparing synchronous and asynchronous interventions and their effects on outcomes such as quality of life, physical fitness, functional capacity, strength, and pain.MethodsRandomised clinical trials and quasi-experimental studies published between 2014 and 2024 were included, totalling 16 studies with 1,416 participants. The interventions varied between synchronous teleexercise (via videoconference) and asynchronous (via apps and recorded videos). The review followed the PRISMA guidelines, ensuring a systematic approach to study selection, data extraction, and bias assessment.ResultsThe results indicate that tele-exercise, especially synchronous, has the potential to primarily improve physical fitness, functional capacity, and pain perception, being effective for the elderly and individuals with specific conditions such as multiple sclerosis and obesity.DiscussionHowever, the methodological heterogeneity of the studies and the lack of consistent data limit the generalisation of the findings, highlighting the need for more high-quality research.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024563241, PROSPERO (CRD42024563241).